1
$\begingroup$

a. $10e^{2x}=7\cdot 2^{ax}$

b. $\frac{2(a-x)}{3\sqrt[3]{x}}-x^{2/3}=0$

I did both, but I'm not sure if I did them correctly. Here is my work for both questions:

a. $10e^{2x}=7\cdot 2^{ax}$

$e^{2x}=\frac{7\cdot 2^{ax}}{10}$

$In(\frac{7\cdot 2^{ax}}{10})=2x$

$In(\frac{7}{10})+In(2^{ax})=2x$

$In(\frac{7}{10})+axIn(2)=2x$

$In(\frac{7}{10})=2x-axIn(2)$

$In(\frac{7}{10})=x(2-aIn(2))$

$x=\frac{In(\frac{7}{10})}{2-aIn(2)}$

b. $\frac{2(a-x)}{3\sqrt[3]{x}}-x^{2/3}=0$

$\frac{2(a-x)}{3\sqrt[3]{x}}=x^{2/3}$

$2(a-x)=3x^{1/3}\cdot x^{2/3}$

$2(a-x)=3x$

$2a-2x=3x$

$2a=5x$

$x=\frac{2a}{5}$

$\endgroup$
4
  • 2
    $\begingroup$ That is Correct $\endgroup$ – user35687 Aug 14 '16 at 18:07
  • $\begingroup$ Thanks. Do you know any better way or faster? $\endgroup$ – 关一骏 Aug 14 '16 at 18:08
  • 2
    $\begingroup$ I think you found the best way to solve them, congratulations! $\endgroup$ – Peter Aug 14 '16 at 18:09
  • 3
    $\begingroup$ In the answer below, it is pointed out that we have to be careful in exercise $a)$ (denominator could be $0$) $\endgroup$ – Peter Aug 14 '16 at 18:15
2
$\begingroup$

For (a), the real solution (correct):

$$10e^{2x}=7\cdot2^{\text{a}x}\Longleftrightarrow$$ $$\ln(10e^{2x})=\ln(7\cdot2^{\text{a}x})\Longleftrightarrow$$ $$\ln(10)+\ln(e^{2x})=\ln(7)+\ln(2^{\text{a}x})\Longleftrightarrow$$ $$2x+\ln(10)=\ln(7)+\text{a}x\ln(2)\Longleftrightarrow$$ $$2x-\text{a}x\ln(2)=\ln(7)-\ln(10)\Longleftrightarrow$$ $$x(2-\text{a}\ln(2))=\ln(7)-\ln(10)\Longleftrightarrow$$ $$x=\frac{\ln(7)-\ln(10)}{2-\text{a}\ln(2)}$$

Where $\text{a}\ln(2)\ne2$

(b) is also correct, but $\text{a}\ne0$.

$\endgroup$
9
  • $\begingroup$ You are right with $a)$ . In $b)$ , the case $a=0$ is valid. $\endgroup$ – Peter Aug 14 '16 at 18:14
  • $\begingroup$ @Peter That was what I was pointing out here. $\endgroup$ – Jan Eerland Aug 14 '16 at 18:14
  • 2
    $\begingroup$ Now, look when $a=0$: $$2\cdot\frac{0-x}{3\cdot\sqrt[3]{x}}-x^{\frac{2}{3}}=0\Longleftrightarrow-\frac{5x^{\frac{2}{3}}}{3}=0$$ That gives us a solution at $x=0$, but when we check that: $$2\cdot\frac{0-x}{3\cdot\sqrt[3]{0}}-0^{\frac{2}{3}}$$ $\endgroup$ – Jan Eerland Aug 14 '16 at 18:20
  • 2
    $\begingroup$ @Peter You're welcome, when we use a limit then we can get to zero but it has to be in a carefull way! Otherwise you allowed yourself to divide by zero .... kuch $\endgroup$ – Jan Eerland Aug 14 '16 at 18:22
  • 1
    $\begingroup$ @C.Guan You're welcome! $\endgroup$ – Jan Eerland Aug 14 '16 at 18:29

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.